The Effect of Hypoxia on Platelet Survival and Site of Sequestration in the Newborn Rabbit - Castle, Valerie; Coates, Geoffrey; Mitchell, Lesley G; O’Brodovich, Hugh; Andrew, Maureen (Thrombosis and Haemostasis, 1988)
Thrombocytopenia occurs frequently in sick neonates that have experienced perinatal asphyxia. This study investigated the effect of one component of asphyxia, hypoxia, on platelet life-span and site of sequestration. 11 indium oxine platelet survivals with scintigraphic imaging were performed in newborn and adult rabbits exposed to room air (normoxia) or following exposure to a 15 minute, severe hypoxic insult (FjOa = 0.05). Platelet survivals in normoxic adults (n = 27) and newborn rabbits (n = 11) were similar (60 ± 3.9 hr vs 64 ± 8.0 hr, m ± SEM). Inhalation of 5% oxygen for 15 minutes was not associated with an acidemia and did not produce thrombocytopenia but significantly shortened the platelet survival to 34 ± 3 hr in the adult (n = 18) and 38 ± 3 hr in the newborn rabbit (n = 7). Postmortem measurement of the sites of mIn-platelet accumulation showed that under normoxic conditions the platelets accumulated in the liver and spleen (23 ±4.3% and 8 ± 1.0% of the total body counts) in the adult with even greater accumulation in the liver (58 ± 6.8%) and spleen (19 ± 4.9%) of the newborn (p <0.001). The latter observation was likely due to the relatively increased size of the liver and spleen in the newborn compared to the adult. Hypoxia did not alter the site of platelet sequestration in adults or newborns. Our results suggest that the newborn has the same platelet survival as the adult and that acute, severe hypoxia significantly shortens the survival of platelets in both groups. Although the sites of sequestration are qualitatively the same in the newborn, there is greater sequestration in the liver and spleen when compared to the adult.
Keywords: Hypoxia; Platelet survival